ISOLASI DAN IDENTIFIKASI SENYAWA SAPONIN DARI EKSTRAK METANOL BATANG PISANG AMBON(Musa paradisiaca var. sapientum L.) - Suharto, M. Agung Pratama; Edy, Hosea Jaya; Dumanauw2, Jovie M. (PHARMACON, 2012)
Bananais a plant thatcanbe used asthe basis fortreatment.Banana trunk containssaponincompounds, flavonoids, andtannins.The purpose of this study was to isolate saponin compound in methanol extract of Ambon banana (Musa paradisiaca var. sapientum L.) using preparation of Thin Layer Cromatography method. Identification of absorbance value of saponin was done in maximum wave length using UV-Vis spectrophotometer. Methanol extract of Ambon banana trunk was obtained by maceration. Saponinsis said to be contained in banana trunk if the foam formed is stablewith the height of2-3 cmhighfor 30secondsin the addition ofone drop ofhydrochloricacid2Nandcolor testLiebermannBurchard(LB) whichproducesbrownringindicatestriterpenesaponin.Resultsofisolationusingeluentchloroform: methanol: water (13:7:2) gave the greenstainspotsonsilicagelplatessprayedwith reagentLBso it is saidthat the samplealso containssteroidalsaponinstypeswith Rfvalue of0.275; 0.325; 0.375.Based on theresults ofidentification usingultravioletvisiblespectrophotometry, absorbance valuewas2.754saponinat209nmmaximum wavelength. Keywords: isolation, saponin, methanol extract, Ambon banana trunk